2004
DOI: 10.1086/423937
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses toBacillus anthracisProtective Antigen in Patients with Bioterrorism‐Related Cutaneous or Inhalation Anthrax

Abstract: Anti-protective antigen (PA) immunoglobulin (Ig) G, toxin neutralization, and PA-specific IgG memory B cell responses were studied in patients with bioterrorism-related cutaneous or inhalation anthrax and in a patient with laboratory-acquired cutaneous anthrax. Responses were determined for >1 year after the onset of symptoms. Eleven days after the onset of symptoms (15 days after likely exposure), anti-PA IgG was detected in 16 of 17 patients with confirmed or suspected clinical anthrax who were tested. Anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
116
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 38 publications
7
116
2
Order By: Relevance
“…Binding of PA impedes toxin entry into cells, and is important in neutralizing B. anthracis LT in vivo and in vitro [20]. We and others have shown that there is strong correlation between IgG to PA and toxin-neutralizing activity after human infection with virulent anthrax, and vaccination with AVA [21,22].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Binding of PA impedes toxin entry into cells, and is important in neutralizing B. anthracis LT in vivo and in vitro [20]. We and others have shown that there is strong correlation between IgG to PA and toxin-neutralizing activity after human infection with virulent anthrax, and vaccination with AVA [21,22].…”
Section: Discussionmentioning
confidence: 96%
“…Samples were retrieved from −70 • C storage that met preestablished criteria: (a) Vaccinations must have occurred within defined time intervals after receipt of the initial AVA injection (day 0 [dose #1], day 14 [range [11][12][13][14][15][16][17][18][19][20][21] ). (b) Pre-injection sera were defined as those taken on the day of each vaccine dose.…”
Section: Methodsmentioning
confidence: 99%
“…All serum samples were assayed for anti-PA IgG by ELISA as described [16] with the following modifications: PA antibodies were detected using mAb HP6043 anti-human IgG followed by alkaline phosphatase-labeled rat anti-mouse IgG [17].…”
Section: Assay Proceduresmentioning
confidence: 99%
“…Studies of adaptive immunity to anthrax infection have focused overwhelmingly on serology, with only one study reporting T cell responses to PA (10)(11)(12)(13). Data from animal or human vaccination studies show that the induction of LT-neutralizing Ab by vaccines containing PA correlates with protection (14)(15)(16).…”
mentioning
confidence: 99%